How Discovery Learning Affect Students’ Numeracy? A Case on Statistics Material - Anjani, Erlina; Alyani, Fitri ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2025)
The numeracy skills of students in Indonesia are an important focus, as reflected in the 2022 PISA results. Numeracy skills are a crucial part of the global curriculum, which aims to help learners develop the ability to think logically and understand data, graphs, and mathematical information increasingly relevant in modern life. This study was conducted to examine the impact of the discovery learning approach on students’ numeracy skills, specifically within the context of learning statistical concepts. This research is quantitative research. With a non-equivalent control group and a posttest, this study employed a quasi-experimental design. The experimental class and the control class were conducted in classes X-5 and X-6 at one of the Jakartan high schools utilizing the researchers' sampling technique, purposive sampling. A written test with five questions is used as the data collecting tool in this study to get information on numeracy abilities. The result of this study used logit data processing show that discovery learning. Based on the results of logit data processing which shows that the average value of the experimental class (0.4039) is greater than the control class (0.0697) after treatment. T-test shows a significant difference between the experimental class and the control class with a Sig value. 0.001 <0.05. To strengthen the t-test, researchers analyzed the effect size, obtained a Cohen's d value of 0.835901 with strong criteria. it can be concluded that there is an effect of the discovery learning model through a numeracy approach on students' numeracy skills in statistics.